Tailoring the morphology and surface plasmon coupling of BiVO4 toward efficient visible-light degradation of antibiotic pollutants - Thinh B. Le; Van M. Dinh; Phuong T.M. Ha; Dat H. Nguyen; Thien P. Nguyen; Nhi T. Y Nguyen; Tuan A. Nguyen; YB.N. Tran; Kim-Ngan N. Phan; Hiep Q. Ha; Dai-Viet N. Vo (Environmental Research, 2026)

An undescribed alkaloid from Crinum latifolium L.: structural elucidation and evaluation of its biological activity - Tuan Anh Hoang Le; Ngo Van Hieu; Nguyen Tien Dat; Vu Thi Trang; Pham Van Cong; Do Thanh Tuan; Vinh Le Ba; Lo Van Xanh; Tran My Linh; Pham Thi Hoe; Le Quynh Lien (Natural Product Research, 2026)

Morphological characteristics and molecular identification of Chloranthus nervosus Collett & Hemsl. (Syn. Chloranthus flavus D.T. Liu & G. Chen) from Vietnam - Tran Van Chen; Tran Thi Thuy Quynh; Huynh Thanh Duy; Duong Phan Nguyen Duc; Nguyen Quoc Bao; Hoang Dac Khai; Pham Thi Thanh Dat (Vegetos, 2026)

Regulated-valence Ptδ+ sites on self-reconstructed CoO shell-enriched Co2P/Co9S8 heterostructure nanoarray for robust anion exchange membrane water electrolyzer - Jinhai Yang; Penghao Zhu; Thanh Hai Nguyen; Tan Dat Nguyen; Van An Dinh; Duy Thanh Tran; Nam Hoon Kim; Joong Hee Lee (Chemical Engineering Journal, 2026)

Integrated eDNA and conventional surveys of coral reef fishes at submerged banks, shoals, and offshore Islands in Southern Vietnam - Long Van Nguyen; Quang Minh Thai; Dat Xuan Mai; Thinh Cong Tran; My Thao Nguyen-Le; Hong Kim Thi Phan; Ben Xuan Hoang; Ha Viet Dao; Binh Thuy Dang; Oanh Thi Truong; Sang Quang Tran (Regional Studies in Marine Science, 2026)

Synthesis, characterization, and ethanol vapor sensing characteristics of vanadium-based-MOFs with and without Cu doping - Tan Le Hoang Doan; Tae-Un Kim; Yujin Kim; My Van Nguyen; Ali Mirzaei; Ngoc Xuan Dat Mai; Linh Ho Thuy Nguyen; Hanh-Vy Tran Nguyen; Ha-Van Nguyen; Nhat Minh Quang Tran; Thang Bach Phan; Hyoun Woo Kim; et al. (Chemical Engineering Journal, 2026)

Retraction notice to ‘Construction of S-scheme CdS/g-C3N4 nanocomposite with improved visible-light photocatalytic degradation of methylene blue’ [Environ. Res. 206 (2022) 112556] - Kim Nguyen Van; Ha Tran Huu; Viet Nga Nguyen Thi; Thanh-Lieu Thi Le; Quoc Dat Hoang; Quoc Viet Dinh; Vien Vo; Dai Lam Tran; Yasser Vasseghian (Environmental Research, 2025)

Rapid fabrication of expanded vermiculite with microwave as low-cost adsorbent for removal of arsenic from water - Thu Ha Dao; Duong Duc La; Van Chinh Tran; Manh Ha Nguyen; Duy Dat Nguyen; Van Huy Nguyen; Van Huyen Luu; Thi Hoai Phuong Nguyen (International Journal of Environmental Science and Technology, 2025)

Phytochemical investigation of Crinum asiaticum L.: isolation and characterisation of a new dimeric alkaloid and evaluation of acetylcholinesterase inhibition with molecular docking - Le Quynh Lien; Le Ba Vinh; Vu Thi Trang; Ngo Viet Duc; Nguyen Viet Phong; Seo Young Yang; Nguyen Minh Trang; Ngo Van Hieu; Do Thanh Tuan; Nguyen Tien Dat; Tran My Linh; Pham Thi Hoe; et al. (Natural Product Research, 2025)

Mapping structures obscured by sediments of the southern Hanoi basin using gravity data - Luan Thanh Pham; Korimilli Naga Durga Prasad; Franck Eitel Kemgang Ghomsi; Minh Le-Huy; Saulo P. Oliveira; Dat Viet Nguyen; Kha Van Tran; Thanh Duc Do (Earth Science Informatics, 2025)

Essential oil of the leaves of psychotria asiatica L.: chemical composition, antioxidant, anti-inflammatory, and cytotoxic properties - Tien Dong Tran; Anh Tuan Le; Dat Van Tran; Thang Quoc Le; Ty Viet Pham (Natural Product Research, 2025)

Mapping structural geometry and tectonics of the Central continental margin of Vietnam and adjacent areas using an enhanced horizontal gradient of gravity data - Korimilli Naga Durga Prasad; Dat Viet Nguyen; Minh Le-Huy; Kha Van Tran; Thanh Duc Do; Luan Thanh Pham; Haseeb Rehman (Tectonophysics, 2025)

Chemical constituents from symplocos sumuntia and their anti-inflammatory effect - Tran Thu Huong; Nguyen Van Thong; Tran Anh Quang; Le Huyen Tram; Le Thi Thuy; Nguyen Thi Thuy My; Nguyen Tuan Anh; Nguyen Tuan Hiep; Nguyen Ngoc Linh; Duc-Dat Le; Tran Thu Ha; Bui Van Thanh (Natural Product Research, 2025)

How does bias correction impact simulated drought characteristics by Regional Climate Models? - Phuong Nguyen-Ngoc-Bich; Manh-Hung Le; Tan Phan-Van; Thanh Ngo-Duc; Tuan Tran-Bui-Anh; Long Trinh-Tuan; Huong Ngo-Thi-Thanh; Dat Pham-Tien; Fredolin T. Tangang; Liew Juneng; Faye Cruz; Jing Xiang Chung; et al. (Climatic Change, 2025)

Synthesis and adsorption behavior of Zn₂SiO₄ nanoparticles incorporated with biomass-derived activated carbon as a novel adsorbent in a circular economy framework - Van Thuan Le; Viet Hung Hoang; Hien Y Hoang; Anh Tien Nguyen; Van-Dat Doan; Vy Anh Tran (Biomass and Bioenergy, 2025)

Enhancing the resolution of the edges in interpreting gravity data - Nguyen Ngoc Long; Dat Viet Nguyen; Kha Van Tran; Luan Thanh Pham (Journal of Earth System Science, 2025)

Organophosphate Pesticide Exposure: Effect on Farmers’ Sperm Quality in the Mekong Delta, Vietnam - Hong Lap Nguyen; Quoc Dat Ngo; Van Chinh Nguyen; Kien Duc Ngo; Vinh Nien Lam; Tran Ngoc Dang; Quang Hien Tran; Tri Dung Phung; Kim Trung Nguyen; Truong Vien Nguyen; Bui Thi Hong Loan; Thien Thuan Tran (Journal of Agromedicine, 2024)

Pollution characteristics, associated risks, and possible sources of heavy metals in road dust collected from different areas of a metropolis in Vietnam - Nguyen Duy Dat; Ly Sy Phu Nguyen; Thi-Dieu-Hien Vo; Truc Van Nguyen; Thi Thuy Linh Do; Anh Thi Kim Tran; Nhung Thi-Tuyet Hoang (Environmental Geochemistry and Health, 2023)

Mn3O4/activated carbon nanocomposites for adsorptive removal of methylene blue - Van Thuan Le; Thi Kieu Ngan Tran; Nguyen Khoa Dang; Van Dat Doan; Vy Anh Tran; Yasser Vasseghian; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2023)

Performance of low flux sponge membrane bioreactor treating industrial wastewater for reuse purposes - My Linh Nguyen; Thi-Dieu-Hien Vo; Nguyen Duy Dat; Van-Truc Nguyen; Anh Thi Kim Tran; Phuong-Thao Nguyen; Xuan-Thanh Bui (Bioresource Technology Reports, 2023)

Research and Development Prospects for Sugarcane Industry in Vietnam - Thi-Thao Nguyen; Quoc-Tuan Hoang; Tien-Thanh Nguyen; Tuan-Anh Pham; Anh-Duong Cao; Hong-Duong Pham; Viet-Hung Le; Thu-Trang Vu; Ngoc-Hung Pham; Tien-Cuong Nguyen; Kim-Anh To; Van-Hung Nguyen; et al. (Sugar Tech, 2022)

Secondary metabolites from Valeriana jatamansi with their anti-inflammatory activity - Le Huyen Tram; Nguyen Van Thong; Le Thi Thuy; Nguyen Tuan Anh; Nguyen Hoang Minh; Tran Thi Minh; Nguyen Thi Hong Phuong; Tran Thu Ha; Thi Minh Nguyet Nguyen; Duc Dat Le; Nguyen Dinh Hiep; Jong-Tae Park; et al. (Natural Product Research, 2022)

A new triterpenoid from the stems of Kadsura coccinea with antiproliferative activity - Le Huyen Tram; Tran Thu Huong; Le Thi Thuy; Nguyen Van Thong; Nguyen Tuan Anh; Nguyen Hoang Minh; Tran Thu Ha; Dao Anh Dung; Nguyen Phuong Thao; Phuong Thien Thuong; Duc Dat Le; Nguyen Dinh Hiep; et al. (Natural Product Research, 2022)

Macrotricolorin A, a new diarylpropanoid from the Vietnamese plant Macrosolen tricolor (Lecomte) Danser - Kieu Hung Le; Thi Kim Ngan Bui; Nguyen Kim Tuyen Pham; Van Son Dang; Trong Nghia Ngo; Nhat Minh Phan; Trong Dat Bui; Trong Duc Tran; Quan Hien Nguyen; Quoc Luan Ngo; Dinh Tri Mai; Tan Phat Nguyen (Natural Product Research, 2022)

Contamination, source attribution, and potential health risks of heavy metals in street dust of a metropolitan area in Southern Vietnam - Nguyen Duy Dat; Van-Truc Nguyen; Thi-Dieu-Hien Vo; Xuan-Thanh Bui; Manh-Ha Bui; Ly Sy Phu Nguyen; Xuan-Cuong Nguyen; Anh Thi-Kim Tran; Thi-Tinh-Au Nguyen; Yun-Ru Ju; Thi-Minh-Trang Huynh; Duy-Hieu Nguyen; et al. (Environmental Science and Pollution Research, 2021)

High-efficient reduction of methylene blue and 4-nitrophenol by silver nanoparticles embedded in magnetic graphene oxide - Van-Dat Doan; Ngoc-Vy Nguyen; Thi Lan-Huong Nguyen; Vy Anh Tran; Van Thuan Le (Environmental Science and Pollution Research, 2021)

Antibiotic and antiparasitic residues in surface water of urban rivers in the Red River Delta (Hanoi, Vietnam): concentrations, profiles, source estimation, and risk assessment - Nhu Da Le; Anh Quoc Hoang; Thi Thu Ha Hoang; Thi Anh Huong Nguyen; Thi Thuy Duong; Thi Mai Huong Pham; Tien Dat Nguyen; Van Chung Hoang; Thi Xuan Binh Phung; Huu Tuyen Le; Cao Son Tran; Thu Hien Dang; et al. (Environmental Science and Pollution Research, 2021)

Cytotoxic activity and phytochemical composition of Stereospermum binhchauensis V.S. Dang leaves - Dinh Tri Mai; Trong Nghia Ngo; Ngoc Thien Ly Nguyen; Quoc Luan Ngo; Nhat Phan Minh; Trong Dat Bui; Van Son Dang; Cong Luan Tran; Nguyen Kim Tuyen Pham; Nguyen Minh An Tran; Tan Phat Nguyen (Natural Product Research, 2021)

Markhasphingolipid A, new phytosphingolipid from the leaves of Markhamia stipulata var. canaense V.S. Dang - Trong Nghia Ngo; Nu Dan Phuong Nguyen; Ngoc Thien Ly Nguyen; Nguyen Kim Tuyen Pham; Nhat Minh Phan; Trong Dat Bui; Van Son Dang; Cong Luan Tran; Dinh Tri Mai; Tan Phat Nguyen (Natural Product Research, 2020)

Markhacanasin C, cycloartane triterpenoid from the leaves of Markhamia stipulata var. canaense V.S. Dang - Trong Nghia Ngo; Cong Thin Vo; Nguyen Kim Tuyen Pham; Nhat Minh Phan; Trong Dat Bui; Quoc Luan Ngo; Van Son Dang; Cong Luan Tran; Dinh Tri Mai; Tan Phat Nguyen (Natural Product Research, 2019)

A Novel Cross-Linked Magnetic Hydroxyapatite/Chitosan Composite: Preparation, Characterization, and Application for Ni(II) Ion Removal from Aqueous Solution - Van Thuan Le; Van Dat Doan; Dinh Duc Nguyen; Hoai Thuong Nguyen; Quoc Phu Ngo; Thi Kieu Ngan Tran; Hoang Sinh Le (Water, Air, & Soil Pollution, 2018)

Genetic analysis of 55 northern Vietnamese patients with Wilson disease: seven novel mutations in ATP7B - Le Anh Tuan Pham; Trong Tue Nguyen; Hoang Bich Nga Le; Dat Quoc Tran; Cam Tu Ho; Thinh Huy Tran; Van Thanh Ta; The Hung Bui; Van Khanh Tran (Journal of Genetics, 2017)

Current conservation status of Germain’s langur (Trachypithecus germaini) in Vietnam - Bang Van Tran; Minh Anh Nguyen; Dat Quoc Nguyen; Quan Bich Thi Truong; Andie Ang; Herbert H. Covert; Duc Minh Hoang (Primates, 2017)

A new anti-inflammatory β-carboline alkaloid from the hairy-root cultures of Eurycoma longifolia - Pham Bich Ngoc; Thanh Binh Pham; Hai Dang Nguyen; Thu Trang Tran; Hoang Ha Chu; Van Minh Chau; Jeong-Hyung Lee; Tien Dat Nguyen (Natural Product Research, 2016)

Bioeconomics of mud crab, Scylla paramamosain , culture in Vietnam - Elizabeth H. Petersen; Truong H. Phuong; Nguyen Van Dung; Pham T. Giang; Nguyen K. Dat; Vu A. Tuan; Tran V. Nghi; Brett D. Glencross (Reviews in Aquaculture, 2013)
The results of bioeconomic analysis informed by a survey of 80 small‐scale mud crab farmers in Vietnam are presented in this paper. Mud crab farming in Vietnam is profitable, with net revenue being approximately 135 and 41 million VND/year (USD 7000–USD 2100 per year) in the central and southern regions, respectively. Profitability was significantly higher in the centre compared with the north, as almost three times the biomass is harvested in the centre compared with the south (in turn, due to higher aquaculture area and survival rates). The benefit–cost ratio (the ratio between total revenue and total costs) is 3.55 in the centre and 1.97 in the south. The crabs are fed almost exclusively on low‐value finfish in the centre and the south. Feeding rates were found to be low, with 95% of biomass gain coming from natural feed in the environment rather than supplementary feeding by the farmer. If pellets are to be adopted widely by mud crab farmers, negative perceptions regarding the poor adaptability of mud crab to pellets (northern farmers only), relatively slow growth rates compared with low‐value finfish and lack of availability of pellets need to be overcome.